The remote sensing survey off Malta – approaches to the mapping of an island’s territorial waters - Bravo-Morata Rodríguez, Alberto; Gambin, Timmy (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The Malta Shipwreck Project, conducted by the University of Malta (UM), is aimed at surveying Malta’s territorial waters, in order to create a map of archaeological remains located on the seabed. Since 2018, this work has been executed using an Autonomous Underwater Vehicle (AUV). Its main payload is an Edgetech dual-frequency (600/1600 kHz) Side Scan Sonar. Due to the capabilities of this particular AUV (stability and battery autonomy), it is able to produce images that are of much higher definition than traditional towed systems. Another advantage is the doing away with long turns associated with working with a ‘towed fish’. In this paper the authors highlight the methodology established by the UM’s team, with the aim of being able to document a site in detail from the discovery until verification stages.